Intra-aortic balloon pump (IABP) rescue therapy for refractory cardiogenic shock due to scorpion sting envenomation. (7th February 2016) - D'sa, Shilpa Reynal; Peter, John Victor; Chacko, Binila; Pichamuthu, Kishore; Sathyendra, Sowmya
Abstract: Background : Cardiomyopathy, cardiogenic shock or acute pulmonary oedema are well recognised complications of scorpion sting envenomation occurring in about 1–3% of patients. Current treatment recommendations include afterload reduction using prazosin and improving cardiac contractility with inotropes like dobutamine. We report the use of intra-aortic balloon pump (IABP) as rescue therapy in a patient with refractory cardiogenic shock due to Mesobuthus tamulus (Indian red scorpion) envenomation.Case : A 32-year-old woman was referred 24 h after a scorpion sting. At presentation she was ventilated and in circulatory shock (systolic blood pressure <50 mmHg). After admission, the patient had four cardiac arrests (three episodes of pulseless ventricular tachycardia/ventricular fibrillation and one episode of asystole) over the next few hours. Following resuscitation, despite a combination of dobutamine, noradrenaline, and adrenaline, blood pressure did not improve significantly. In view of persistent tachycardia (heart rate 160/min), catecholamine storm was suspected and prazosin was added. However, shock was refractory. Hence, IABP was considered as rescue therapy. Following initiation of IABP, there was improvement in cardiac function (improved ejection fraction) which translated to weaning of inotropes over 48 h and improved organ function (renal, respiratory) in the next 2–3 d. However, following extubation, on Day 8, she was noted to have features of hypoxic brain injury. This improved gradually. At discharge (Day 30) she was independent for activities of daily living and was able to mobilise without support.Conclusion : IABP could be generally considered as a rescue therapy in refractory cardiogenic shock in envenomations.